Pengaruh Perencanaan Pajak, Struktur Modal, Komisaris Independen Terhadap Tax Avoidance Dengan Ukuran Perusahaan Sebagai Variabel Moderasi - Made Deva Yuliana; Sri Lestari Yuli Prastyatini (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2022)
This observation aims to examine the effect of tax planning, capital structure, and independent commissioners on tax avoidance with firm size as a moderating variable. The sample used in this observation is BUMN agencies listed on the Indonesia Stock Exchange (IDX) in 2019-2021. The dependent variable of tax avoidance is measured by the cash effective tax rate (CETR). The independent variable of tax planning is measured by the effective tax rate (ETR), capital structure is measured by DER, and independent commissioners are measured by IC. The moderating variable is measured by size. This observation uses a purposive sampling method in sampling. Using multiple regression data analysis techniques, this observation states that tax planning has no effect on tax avoidance. While the capital structure and independent commissioners have a significant influence on tax avoidance. In addition, tax measures cannot strengthen the relationship between tax planning and tax avoidance. Capital structure and independent commissioners can be moderated by agency size. Keywords: Tax Planning, Capital Structure, Independent Commissioner, Tax Avoidance and Company Size